Current Understanding of the Pivotal Role of Mitochondrial Dynamics in Cardiovascular Diseases and Senescence - Uchikado, Yoshihiro; Ikeda, Yoshiyuki; Ohishi, Mitsuru (Frontiers in Cardiovascular Medicine, 2022)
The heart is dependent on ATP production in mitochondria, which is closely associated with cardiovascular disease because of the oxidative stress produced by mitochondria. Mitochondria are highly dynamic organelles that constantly change their morphology to elongated (fusion) or small and spherical (fission). These mitochondrial dynamics are regulated by various small GTPases, Drp1, Fis1, Mitofusin, and Opa1. Mitochondrial fission and fusion are essential to maintain a balance between mitochondrial biogenesis and mitochondrial turnover. Recent studies have demonstrated that mitochondrial dynamics play a crucial role in the development of cardiovascular diseases and senescence. Disruptions in mitochondrial dynamics affect mitochondrial dysfunction and cardiomyocyte survival leading to cardiac ischemia/reperfusion injury, cardiomyopathy, and heart failure. Mitochondrial dynamics and reactive oxygen species production have been associated with endothelial dysfunction, which in turn causes the development of atherosclerosis, hypertension, and even pulmonary hypertension, including pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. Here, we review the association between cardiovascular diseases and mitochondrial dynamics, which may represent a potential therapeutic target.